Development of a brain-permeable peptide nanofiber that prevents aggregation of Alzheimer pathogenic proteins - Tanaka, Naoki (PLoS One, 2020)
Alzheimer's disease (AD) is proposed to be induced by abnormal aggregation of amyloidβ in the brain. Here, we designed a brain-permeable peptide nanofiber drug from a fragment of heat shock protein to suppress aggregation of the pathogenic proteins. To facilitate delivery of the nanofiber into the brain, a protein transduction domain from Drosophila Antennapedia was incorporated into the peptide sequence. The resulting nanofiber efficiently suppressed the cytotoxicity of amyloid βby trapping amyloid β onto its hydrophobic nanofiber surface. Moreover, the intravenously or intranasally injected nanofiber was delivered into the mouse brain, and improved the cognitive function of an Alzheimer transgenic mouse model. These results demonstrate the potential therapeutic utility of nanofibers for the treatment of AD.